Blood pressure variability, nocturnal heart rate variability and endothelial function predict recurrent cerebro-cardiovascular events following ischemic stroke - Filchenko, Irina; Mürner, Nicolas; Dekkers, Martijn P. J.; Baillieul, Sebastien; Duss, Simone B.; Brill, Anne-Kathrin; Horvath, Thomas; Heldner, Mirjam R.; Rexhaj, Emrush; Bernasconi, Corrado; Bassetti, Claudio L. A.; Schmidt, Markus H. (Frontiers in Cardiovascular Medicine, 2023)
Introduction Cardiovascular parameters characterizing blood pressure (BP), heart rate (HR), endothelial function and arterial stiffness predict CCVE in the general population. Considering the paucity of data in stroke patients, we assessed these parameters as potential predictors of recurrent CCVE in acute stroke and at 3 months post-stroke. Patients and methods This is a secondary outcome analysis of a prospective observational longitudinal Sleep Deficiency & Stroke Outcome Study (ClinicalTrials.gov Identifier: NCT02559739). The study consecutively recruited acute ischemic stroke patients. Cardiovascular parameters were assessed within the first week post-stroke. Future CCVE were recorded over a 3-year follow-up. Multivariate Cox regression analysis was used to investigate the prognostic value of 48 cardiovascular parameters regarding CCVE risk. Results Out of 447 recruited patients, 359 were included in this analysis. 20% of patients developed a future CCVE. A high variability of systolic BP (n=333) and nocturnal HR (non-linear parameters; n=187) at acute stroke predicted CCVE risk after adjustment for demographic parameters, cardiovascular risk factors and mean BP or HR, respectively. Endothelial dysfunction (n=105) at acute stroke predicted CCVE risk after adjustment for age and sex, but not after adjustment for cardiovascular risk factors. Diurnal HR and arterial stiffness at acute stroke were not associated with CCVE risk. Conclusion High blood pressure variability, high nocturnal HRV and endothelial function contribute to the risk for future CCVE after stroke.